Dramatic Storytelling and Narrative Design A Writer's Guide to Video Games and Transmedia. - Berger, Ross. (Milton : CRC Press LLC, 2019)
This book provides an industry professional's firsthand POV into narrative design's practical usage, day-to-day roles and responsibilities, and keys to breaking in and succeeding. The book will also delve into the foundations of compelling storytelling through structural analysis and character archetype breakdowns. The author widens the understanding of game narrative to include examples from other media. He will also break the structure down of two popular games and show how the structural elements are applied in practice. In addition to discussing industry trends (including Fortnite, Twitch, and Netflix's interactive TV shows), the author illustrates how the leveraging of transmedia can make a video game franchise enduring over time. Because media appetites are radically changing, designing a story experience across various media outlets is not only preferable to meet the high demands of millennial and GenZ consumers; it's necessary as well. Key Features: Practical how-to's to meet the ever-increasing studio demands for a narrative designer Critical analysis of the narrative of two best-selling games Samples of a story structure diagram, character polling, transmedia release timeline, and a branching conversation tree Deep breakdowns and definitions of story beats and dramatic devices Pro-tips on better documentation and overall job preparedness
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Computer Graphics / Game Programming & Design; Video games -- Authorship